2022
DOI: 10.3390/jcdd9100355
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Valve Function after Aortic Valve Replacement for Severe Aortic Stenosis by Transcatheter Procedure versus Surgery

Abstract: Background This study compared the clinical outcomes of transcatheter (TAVR) and surgical (SAVR) aortic valve replacements, focusing on postoperative valvular performance assessed by echocardiography. Method and Results A total of 425 patients who underwent TAVR (230 patients) or SAVR (195 patients) were included. Postoperative effective orifice area index (EOAI) was higher in the TAVR group (1.27 ± 0.35 cm2/m2) than in the SAVR group (1.06 ± 0.27 cm2/m2, p < 0.001), and patient–prosthesis mismatch (PPM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Padang et al [19] demonstrated that mild and tract PVL had a lower survival rate (50.9%) compared to no PVL (62.7%) at 5 years. In a recent study, Saito et al [20] showed that mild or greater PVL had significantly lower freedom from events (70 months) compared to trace and no PVL. Additionally, PVL severity has been shown to be related to hemolysis rates [21].…”
Section: Introductionmentioning
confidence: 97%
“…Padang et al [19] demonstrated that mild and tract PVL had a lower survival rate (50.9%) compared to no PVL (62.7%) at 5 years. In a recent study, Saito et al [20] showed that mild or greater PVL had significantly lower freedom from events (70 months) compared to trace and no PVL. Additionally, PVL severity has been shown to be related to hemolysis rates [21].…”
Section: Introductionmentioning
confidence: 97%